Making Digital Elevation ModelsAccessible, Comprehensible, and Engaging through Real-Time Visualization - Thomas Kjeldsen; Peter Trier Mikkelsen; Jesper Mosegaard (Geoforum Perspektiv, 2016)
In this paper we present our initial experiments with the new high quality digital elevation model, “Danmarks Højdemodel-2015” (DHM) exposed as an interactive 3D visualization on web and in virtual reality. We argue that such data has great opportunities to spawn new business and new insight for the individual citizen if it is accessible, comprehensible and engaging.